Problematika Peran Ganda Wanita Karir: Strategi Bimbingan dan Konseling dengan Konseling Feminist dalam Mengatasi Tantangan - Jannah, Miftahul; Afdal, Afdal; Hariko, Rezki (Institut Agama Islam Negeri Kerinci, Indonesia, 2024)
Married career women often have their own challenges in carrying out their duties and responsibilities. Not only prioritizing work matters, career women must also prioritize their duties and responsibilities as housewives. So the purpose of writing this article is to find out what problems are often experienced by career women who have dual roles as women who work outside the home and as housewives and how to overcome them using feminist counseling. The method in this research uses library research by collecting various articles related to the topic discussed. The research results show that by dividing and organizing good time management by women who have multiple roles, they can overcome the problems they experience and by providing guidance and counseling services, counselors can help through feminist counseling. Feminist counseling services help career women to have confidence in their abilities in carrying out their duties as career women and housewives. Future researchers are advised to conduct more in-depth case studies and use more complex methods.